Pelaksanaan Program Sekolah Ramah Anak Dalam Membentuk Etika Sosiak Remaja Sekolah Menengah Pertama - Tajwa Raya Rabani; Nadya Putri Saylendra; Erwin Susanto (PT PUSTAKA CENDEKIA GROUP, 2026)
This study is motivated by the importance of developing students’ social ethics amid increasing social behavior problems in schools. The research aims to analyze the implementation of the Child-Friendly School Program in shaping students’ social ethics at SMPN 5 Karawang Barat. This study employs a qualitative approach with a descriptive method. Data were collected through interviews, observations, and documentation, and analyzed using the Miles and Huberman model. The findings reveal that various activities within the program, such as habituation practices, classroom learning, extracurricular activities, religious activities, and counseling services, contribute to fostering values of politeness, tolerance, discipline, responsibility, and social awareness. The program also creates a safe and supportive school environment that encourages positive social interaction. Therefore, the Child-Friendly School Program not only functions as a child protection policy but also serves as an effective pedagogical strategy in developing students’ social ethics holistically.